Analyzing Microstructural Features, Surface Topography, and Scratch Resistance of Innovative Nano-Composites Coated with High Velocity Air-Fuel Technology (Fracture and Structural Integrity, 2023)
New developments in thermal spraying processes may offer higher-quality alternatives to hard chrome plating and possibilities for hard chrome plating in a range of coating applications. These include spraying with high-velocity air fuel (HVAF) and new spray consumables. The low operating temperatures and accelerated particle velocity of the HVAF process enable investigation and development of a wide range of novel coating materials and applications. The High-velocity Air Fuel Process' quality and efficiency are primarily due to the broad combustion chamber and axial injection of the feedstock through it, as well as the relatively low combustion temperature of an air-fuel mixture and the low gas velocity that provides enough time for the mild heating of the powder particles. The current work discusses the inventive thermal spray procedure used for SAE 1008 carbon steel, a cost-effective substrate material. All of the compositions that were treated have undergone microstructure investigations. A scratch test is conducted in accordance with ASTM guidelines. Assessment of surface morphology clearly demonstrates the relationship between the evaluated parameters. According to the occurrence, scratch methods such as delamination, cracking, plastic deformation, and elastic deformation are highlighted. However, the findings of the scratch test showed that the samples' scratch resistance increased as the coating thickness rose. In comparison to samples with thinner coating, those with thicker coating demonstrated a stronger resistance to scratching. This is explained by the fact that coatings with a higher thickness and density can support the subsurface more effectively and stop cracks from scattering. This can retain the coating's integrity and stop more damage from occurring, improving scratch resistance. Better scratch resistance was displayed by the samples with denser microstructures and smoother surface morphologies.The outcome is greater scratch resistance because a higher density covering can withstand deformation and fracture better than a lower density layer. This is due to the mechanism of deformation and fracture in the coating material. This improvement in scratch resistance can be due to the composites' increased HVAF coating's hardness and adherence. The findings imply that using an HVAF coating to increase the scratch resistance of new nanocomposites may constitute a successful strategy.
Keywords: Scratch test; HVAF; microstructural analysis; Microstructure